PHYTOCHEMICAL SCREENING AND ANTIOXIDANT POTENCY OF ADHATODA VASICA AND VITEX NEGUNDO - KUMAR, MANOJ; KUMAR, AMIT; DANDAPAT, SUKUMAR; M. P. SINHA, (The Bioscan, 2013)
The leaf samples of Adhatoda vasica and Vitex negundo were subjected to phytochemical analysis. Both the plants contained antioxidant phytochemicals such as alkaloids, tannin, saponins, phenolics and flavonoids; which were present in comparatively higher amount in Vitex negundo. Tannins were recorded highest among all the phytochemicals (93.9 ± 0.8 and 61.3 ± 0.8 mg/g in Vitex negundo and Adhatoda vasica respectively). Phenolics were recorded lowest (13. ± 0.1 and 8.1 ± 0.5 mg/g in Adhatoda vasica and Vitex negundo respectively.The methanolic extracts of the plants were also analyzed for antioxidant and reducing power potentiality. Both plants showed strong antioxidant and reducing power ability. The strong antioxidant and reducing power ability of the plant underlines their use as antioxidant supplement against diseases such as typhoid during which antioxidant system fails; cardiovascular diseases which are caused due to accumulation of Reactive oxygen species; ageing related diseases, Alzheimer, Prkinson’s disease, Amytrophic lateral sclerosis, cataractogenesis and other diseases.